NAVIGATING LEGAL AND CULTURAL BARRIERS: THE FIGHT FOR GENDER EQUALITY IN PAKISTAN - Shahzeb Danish; Aleesha Abbas; Muhammad Jazib Niaz; Insha; Abdul Rehman (International Journal of Contemporary Issues in Social Sciences, 2024)
Many legislations have been made up till now to provide women equal rights and opportunities as men, but gender equality is still a significant challenge for Pakistan. This article sheds light on the intricacies and impediments of gender parity within Pakistani legal arenas. This point emphasizes the significant challenges these laws face, cultural norms, and application failures around their implementation being key amongst them, as are different religious interpretations. The analysis also reflects the recent legislative initiatives impacting women’s empowerment in multiple dimensions, such as education, employment, and political participation. Results emphasize the requirement for a multi-faceted strategy that includes legal reforms and societal also transformation if gender equality is to be realized in Pakistan.